En déroute. Enquêter non loin de la centrale de Fukushima Daiichi, Japon - Sophie Houdart (Sociologies, 2020)
In this article, I look back over the maze of an investigation conducted in Fukushima prefecture since 2012. Initiated classically as an investigation into the programs for measuring radioactivity in the air, soil and food through which the inhabitants were learning to experience their new living conditions after the triple disaster that occurred on 11 March 2011, it was diverted by a number of episodes that highlighted a disturbed regime of apprehension of the real, both from the point of view of the people involved and that of the investigator. Taking note of these successive disruptions, I describe how the changes in the methods used in the field were linked to the very object in question: life in contaminated territory.